ANALISIS KECERDASAN INTERPERSONAL SISWA YANG MENGALAMI PERUNDUNGAN VERBAL (VERBAL BULLYING) DI KELAS 4 SD NEGERI BORO KECAMATAN KEDUNGWARU - Rahmad Setyo Jadmiko, Yunita Ningtyas, (Universitas Negeri Malang, 2021)
This study aims to determine (1) describe the interpersonal intelligence of students who experience bullying through words at SD Negeri Boro. (2) Describe the form of bullying through words that occurred at SD Negeri Boro. The factors that influence students' interpersonal intelligence are bullying, students' (biological) ancestry and students' socio-emotional development. This is a clear picture of the dangers of bullying. This type of research is qualitative and the approach used is descriptive. The subjects in this study were grade 4 students and homeroom teachers. Methods of data collection using questionnaires, interviews and documentation. The results of the study concluded that the interpersonal intelligence of students who experienced bullying had a significant impact on 7 grade IV students. There are 4 students with high verbal bullying which results in low interpersonal intelligence. As a result, some students experience problems in interacting and socializing with their peers.